2005
DOI: 10.1016/j.pss.2004.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Resorption process in Astypalaea Linea extensive region (Europa)

Abstract: Whereas numerous extensive features, where new crust is created, are now well recognized on Europa's surface, those relevant to crust disappearance remain difficult to find. This work presents a reconstruction of the surface prior to Astypalaea Linea's emplacement (one of the features where new crustal material appears). We demonstrate that a scattered disappearance of crust takes place in an extensive region close to Astypalaea Linea. Physical processes invoked for disappearance are discussed: pressure meltin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…However, Voyager and more recently Galileo's images reveal a surface widely disturbed by "geological" features (Lucchitta and Soderblom, 1982;Greeley et al, 2000;Figueredo and Greeley, 2000). These observations suggest that processes have driven movements in the icy crust in the past and possibly recently and have refreshed the surface 1999;Mével and Mercier, 2005). This last point is supported by the lack of impact craters compared to Ganymede and Callisto implying a young mean surface age ranging from 30 to 70 Myr (Zahnle et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…However, Voyager and more recently Galileo's images reveal a surface widely disturbed by "geological" features (Lucchitta and Soderblom, 1982;Greeley et al, 2000;Figueredo and Greeley, 2000). These observations suggest that processes have driven movements in the icy crust in the past and possibly recently and have refreshed the surface 1999;Mével and Mercier, 2005). This last point is supported by the lack of impact craters compared to Ganymede and Callisto implying a young mean surface age ranging from 30 to 70 Myr (Zahnle et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…For a viscosity contrast in the range 102104, sluggish‐convection operates and produces a relatively fast resurfacing. While ongoing global‐scale surface mobility is reported in the case of Europa (Howell & Pappalardo, ; Kattenhorn & Prockter, ; Mével & Mercier, ), it has been argued that convective processes might not be responsible for this mobility (Howell & Pappalardo, ). Sluggish‐lid regime is therefore probably not pertinent for ice shells.…”
Section: Ice Layer As a Tidally Heated Convective Systemmentioning
confidence: 99%
“…Several mechanisms have been proposed for the accommodation of contractional strain on Europa. In some locations, tectonic reconstructions of Europa's surface (i.e., realigning regions that have undergone lateral offset and/ or spreading) suggest regions of ''missing'' surface material (e.g., Sarid et al, 2002;Mével and Mercier, 2005). These missing regions, dubbed ''convergence bands,'' imply a loss of crustal material during surface contraction.…”
mentioning
confidence: 99%
“…These missing regions, dubbed ''convergence bands,'' imply a loss of crustal material during surface contraction. The strain accommodated in these convergence bands may be large; e.g., Mével and Mercier (2005) suggest the accommodation of $10% contraction. and Greenberg (2004) have also suggested that dilational bands themselves may act as zones of weakness that can accommodate contraction (as much as 75% at Corick Linea (Greenberg, 2004;Kattenhorn and Hurford, 2009)) if the local stress regime changes from tensile to compressional.…”
mentioning
confidence: 99%